Florida state parks: A CHAID approach to market segmentation. Issue 2 (3rd April 2021) - Díaz-Pérez, Flora M.; Fyall, Alan; Fu, Xiaoxiao; García-González, Carlos Gustavo; Deel, Gary
ABSTRACT: This study identifies those market segments that frequent state parks in Florida and, in particular, determines those segmentation "clusters" with a best fit for frequency of visitation, accommodation, and age. Two-Step Cluster Analysis and CHAID approaches to the determination of market segmentation are used. This study demonstrates the precision and multi-tree nature of CHAID analysis in that it offers additional levels of variation and distinctiveness for those marketing and managing tourism generally, and in the specific context of state parks. Rather than managing a homogenous "rural tourist", through CHAID analysis, state parks can benefit from the fine-tuning of marketing messages, the more effective provision and location of accommodation stock, and enhanced efforts to attract out-of-state visitors.